20 Century vs. 21 Century C&C: The SPUR Manifesto. - Patterson, David A. (Communications of the ACM, 2005)
This article focuses on the potential opportunities of computer and communication technologies (C&C) in the 21st century. In 20th century C&C was not particularly concerned about dependability in the drive toward faster and cheaper. On the software side, the emphasis was turning the advances in performance and capacity into more features rather than improving software quality. The hardware side had similar priorities. For example, the original personal computer (PC) included parity memory protection, which requires extra memory. Personal computers were invented about a dozen years later. The argument was since a PC is used by only one person, we didn't need the protection found in traditional operating systems, there was no need to separate administrators from users. The focus was making many PCs, and then on making them faster and cheaper. Computer designers today believe that they have exploited almost all the available implicit parallelism given the available power budget. Indeed, after canceling its uniprocessor projects last year, Intel said the future of high performance microprocessors was multiple processors per chip.